Terminal cancer patients in palliative care: a view to the patient and the family (Research, Society and Development, 2022)
Objective: The objective of this review article is to understand the feelings and perception of the patient and family in the reality of terminal cancer. Methods: This integrative review is composed of scientific articles available on the topic "Perception of the terminal cancer patient in palliative care". For this result, we used as a source of research the Virtual Health Library (VHL) through the databases: Scientific Electronic Library Online (Scielo), PubMed and Latin American and Caribbean Literature on Health Sciences (LILACS). Results: The following discussion was grouped: feelings and perception of patients and family members about cancer and terminality, spirituality and religion in the context of terminality, and feelings and perception of the nursing team regarding the terminally ill patient. Final Considerations: After the diagnosis of terminal cancer, the patient and family members experience various types of feelings and new perceptions arise within this scenario of terminality, something that also occurs with the nursing team that works providing the necessary assistance. In this way, it is possible to understand situations and reactions in this scenario of terminality, and also to add the emphasis of disciplines and teachings focused on this subject of the finitude of life during graduation for a better performance by professionals.